Factors Influencing Military Personnel Utilizing Chaplains: A Literature Scoping Review - Layson, Mark D. (Journal of religion and health, 2022)
Chaplains have been embedded in military settings for over a millennium. In recent years however, the decline in spiritual/religious (S/R) affiliation of military personnel across Western cultures has led to some commentators questioning the utilization of religious chaplains by defence personnel. This scoping review maps the literature on S/R and non-S/R factors that influence utilizing military chaplains—with a particular emphasis on the Australian military context. A systematic scoping review of tertiary literature databases using Arksey and O’Malley (2003) and Joanna Briggs Institute methodologies (JBI, 2021), revealed a total of 33 articles meeting the inclusion criteria. Results fell into three broad categories: (i) how personal religious views influence utilization of military chaplaincy, (ii) barriers and enablers to personnel utilizing military chaplains, and (iii) the impact of chaplaincy. Despite the current reduction in religiosity in Western society, findings from this scoping review suggest there is little evidence that low religiosity among military personnel forms a significant barrier to utilizing chaplaincy services. To the contrary, the literature revealed that chaplains provide trusted, confidential, and holistic support for military personnel that if diminished or compromised would leave a substantial gap in staff well-being services.